Role of Portuguese community pharmacy and pharmacists in self-care - Alves da Costa, F. (2023)
Portugal recognizes the importance of self-care in its policies and has been actively engaging in health literacy and citizen empowerment. The current National Health Plan for the period 2021–2030 clearly mentions the need to “take greater advantage of the network of community pharmacies throughout the national territory, in favour of the health of the community, from the protection and promotion of health, through health literacy, to the prevention and early detection of disease, and the aggravation of chronic disease, among others”. There is recognition of the role of pharmacists and community pharmacies. However, more needs to be done to promote intersectoral collaboration, particularly as community pharmacies are private entities but can nonetheless support the public national health service. Community pharmacies assisted many individuals during the pandemic to test suspect cases free of charge. The fight to end AIDS and viral hepatitis is another example where community pharmacies promote self-testing and ensure efficient screening and referral to diagnosis and treatment. Portugal has already moved to reimburse community pharmacies for services with some of them in areas of self-care including COVID-19 testing. Nevertheless, future challenges include making community pharmacies sustainable. Taking into account that community pharmacies are private entities that can supplement the public health service just as any other provider, it is essential to review payment models, referral mechanisms and access and integration of information from other partners in primary and secondary care.